PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS XI MIA 1 SMA BABUSSALAM PEKANBARU - Susanti, Dewi; Maimunah, Maimunah; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research to improve the learning process and the student’s mathematical understanding skill by implementation Discovery Learning (DL) model. The type of this research is Classroom Action Research with two cycles. The subjects of this research were students of class XI MIA 1 SMA Babussalam Pekanbaru. This study was conducted in the even semester of academic year 2018/2019. The research instruments used are learning material (Syllabus, Lesson Plan, and Student Worksheet) and instrument for collecting data (Observation Sheets and Mathematical Understanding Tests). The observation sheets were used to find out the data of students and teacher activity during learning process which would analyzed qualitatively, and mathematical understanding test were used to collect the student’s mathematical understanding skill outcomes which would analyzed quantitatively. Base on the analysis of the observation sheets showed that implementation of learning process in 2nd cycle was improved when compared to 1st cycle. Result of the test indicates that the student’s learning achievement for the first is 52,08 improved in 1st cycle to 68,75 and improved to 84,26 in 2nd cycle. The improvement of student’s learning achivement founded for each indicator of mahematical understanding skill: (1) redefine the concept; (2) provide examples and not examples the concept; (3)use, utilize, choose certain procedures or operations; and (4) apply problem solving algorithms or algorithms. Based on the result above, it can be concluded that the implementation of Discovery Learning model approach can improve the learning process and the student’s mathematical understanding skill outcomes at class XI MIA 1 SMA Babussalam Pekanbaru.Key Words: Mathematical Understanding Skill, Discovery Learning Model, Classroom Action Research